Integrating Sangiran Early Man Site Museum to Project-Based Learning in Science Course: The-Earth Materials - Rindi Liskasari; Soeparmi Soeparmi; Puguh Karyanto (Journal of Education and Learning (EduLearn), 2018)
The purpose of this study is to explain the benefits of integrating Sangiran Early Man Site Museum and Project-based Learning in The-Earth Material in Science. Twenty-eight seventh grade Junior High School students in Karanganyar, Central Java follow this course in the second semester in the academic year of 2016/2017. The students work in teams to do the project based on their observation and analysis on the phenomena in Sangiran. The researchers use a mixed method research approach to analyze this research by using questionnaire and interview to obtain data on students’ responses to the course. The conclusions of our study are: 1) this course is successful in developing of research skills, teamwork and group discussions; 2) students are not accustomed to learn independently and to learn by using scientific approach; 3) students faces difficulties in making project report and in doing presentation. 4) Project-based-learning can be used as a media to help the students to know about local wisdom in their motherland